Contribuição do exame de imagem para avaliação de pacientes com deficiência de alfa-galactosidase A - Neves, Rodrigo Fernandes de Carvalho Azambuja [UNIFESP] (2018)
Introduction: Alpha-galactosidase A (α-GalA) deficiency is more commonly referred to as Fabry's disease. It is a rare, recessive, X-linked disease caused by mutations in the gene encoding the lysosomalα-GalA enzyme, which affects glycosphingolipid metabolism, as a result of deficient activity of this enzyme, leading to the progressive accumulation of its substrate in plasma and various types of cells, including kidney cells. Renal impairment in such disease is known as well as its progressive nature, but there are still many gaps in relation to the nature of the renal involvement and the manner, moment and intensity with which the different compartments are affected. There are few descriptions directed to the presence, frequency and type of renal cysts found in this disease, motivating the accomplishment of the present study. Objectives: In patients of both genders with α-GalA deficiency, establish: frequency of the occurrence of renal cysts and their characteristics; possible association between these findings and theFabry's disease genotype. Patients and Methods: We compared consecutive patients with Fabry's diseaseand patients with glomerulopathiestreated at UNIFESP, using abdomen ultrasonography, with an active search for cystic formations and detailed evaluation of the kidneys, as well as of demographic, clinical and laboratory data. Results: Individuals with Fabry’s disease and patients with different glomerulopathies with varying glomerular filtration rates were compared. We observed that the groups evaluated were statistically similar, regarding age, gender, glomerular filtration rate estimated by the CKD-EPI formula and stages of chronic kidney disease. When we evaluated the sonographic findings, parapelvic cysts were more frequent in patients with Fabry's disease and this difference was statistically significant in each separate kidney and in both kidneys as well. There was no difference between the group with Fabry's disease and that with other glomerulopathies in relation to the frequency of cortical cysts or other characteristics of the ultrasound examination. The frequency of parapelvic cysts in patients with Fabry's disease and other glomerulopathies was 40.5% vs. 8.9% (and parapelvic associated with cortical cysts was52.4% vs. 10.7%). The finding of parapyelic cysts was not related to the occurrence of Fabry's diseasedefining mutations. Conclusions: In patients with Fabry's disease at different stages of renal involvement, the detection of parapelvic cysts was statistically more frequent than in patients with glomerulopathies and comparable glomerular filtration. This finding may be a further evidence of Fabry's disease in patients with renal disease of undefined etiology when patientsarereferredtoultrasoundexaminationin the investigation of a renal disease, in particular in cases of familial nephropathy.